Market share of credit facilities and their impact on the profitability of banks in the Kingdom of Saudi Arabia – An applied study on Saudi banks – - Al- Qahtani, Amal Abdullah Abdullah (Journal of Economic, Administrative and Legal Sciences, 2020)
The objective of this study is to reveal the effect of the market share of credit facilities on the rate of return on assets and the rate of return on equity in Saudi banks. The study sample consisted of all Saudi banks, which included twelve banks listed on the stock market of 2008 and before 2018. The study relied on the analytical descriptive approach by using the Panel Data Analysis.One of the main findings of the study is that the market share positively affects the rate of return on assets, while the market share of credit facilities does not affect the rate of return on equity. Among the most important recommendations in the study is the need to reduce the rate of return on credit facilities, which may contribute to increasing its market share, which will increase the contribution to the achievement of profits and work on the balance between liquidity and profitability by maintaining the market share in the volume of deposits to give the bank the ability To increase credit facilities and thus increase profits in banks and to conduct further research related to the market share of credit facilities in Saudi banks.
Keywords: credit facilities; return on assets; equity; bank profitability; market share